2014
DOI: 10.1039/c3mb70501c
|View full text |Cite
|
Sign up to set email alerts
|

A global investigation of gene deletion strains that affect premature stop codon bypass in yeast, Saccharomyces cerevisiae

Abstract: Protein biosynthesis is an orderly process that requires a balance between rate and accuracy. To produce a functional product, the fidelity of this process has to be maintained from start to finish. In order to systematically identify genes that affect stop codon bypass, three expression plasmids, pUKC817, pUKC818 and pUKC819, were integrated into the yeast non-essential loss-of-function gene array (5000 strains). These plasmids contain three different premature stop codons (UAA, UGA and UAG, respectively) wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
50
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(50 citation statements)
references
References 37 publications
0
50
0
Order By: Relevance
“…Besides its role in mRNA translation revealed by our group (6) and others (39), OLA1 has been implicated in DNA damage response (8), oxidative response (9), cell adhesion (40), and heat shock (13). In one recent report, OLA1 has been shown to localize not only in cytoplasm but also in the centrosome and spindle poles.…”
Section: Discussionmentioning
confidence: 87%
“…Besides its role in mRNA translation revealed by our group (6) and others (39), OLA1 has been implicated in DNA damage response (8), oxidative response (9), cell adhesion (40), and heat shock (13). In one recent report, OLA1 has been shown to localize not only in cytoplasm but also in the centrosome and spindle poles.…”
Section: Discussionmentioning
confidence: 87%
“…In this study, OLA1 was reported to control protein synthesis and cell fate decisions in stressed cells as well as impacts the growth and progression of the tumour . Another study demonstrates the role of OLA1 in translation regulation thus identifying OLA1 as one of the three candidate genes important for cytoplasmic protein biosynthesis in yeast …”
Section: Introductionmentioning
confidence: 77%
“…However, our findings establish the downstream signalling mechanisms that are involved in OLA1‐mediated decrease in hypertrophic response. OLA1 possesses GTPase and ATPase activities and has been shown to play a role in protein translation and synthesis . Previous reports have shown that OLA1 mediates GSK3β phosphorylation (Ser9) in lung cancer .…”
Section: Discussionmentioning
confidence: 99%
“…2C). Ola1, a superaggregating cytosolic protein previously implicated in translation termination (Samanfar et al, 2014), also forms foci colocalized with Pab1. These four proteins are all thus bona fide heat shock granule components.…”
Section: Resultsmentioning
confidence: 99%